Reimagining South African political campaigns through indigenous language posters in the 4IR: A political communication perspective - Fulufhelo Oscar Makananise (Communicare)
This study sought to explore how the Fourth Industrial Revolution tools or platforms such as digital media technology, social media, and the internet are employed to publicise indigenous language posters for political election campaigns in South Africa. The study was underpinned by a theory of communication in political campaigns to ascertain the importance of communication or linguistic features in political campaign posters. A phenomenological qualitative research method and exploratory research design were employed to address the research problem and objectives of the study. Furthermore, a semi-structured interview was used to collect data from 10 purposively selected respondents. The collected data were thematically analysed to identify, describe, and explain the major themes and sub-themes that emerged. The study established that the previously disadvantaged and marginalised South African indigenous languages were seriously underutilised for political election campaign posters on social media platforms by various South African political organisations. Therefore, the article recommends that, in the context of the Fourth Industrial Revolution, for political parties to participate in the development, preservation, digitalisation, and promotion of these indigenous languages, they should strive to use and post on social media accounts political election campaign posters that are written in the various South African indigenous languages.